2010
DOI: 10.1037/a0018668
|View full text |Cite
|
Sign up to set email alerts
|

Importance of race and ethnicity: An exploration of Asian, Black, Latino, and multiracial adolescent identity.

Abstract: This mixed-method study used a grounded theory approach to explore the meanings underlying the importance adolescents attach to their racial-ethnic identities. The sample consisted of 923 9 th -12 th grade students from Black, Latino, Asian, and Multiracial backgrounds. Thematic findings identified a broad range of explanations for adolescents' racial-ethnic centrality, ranging from pride and cultural connection to ambivalence and colorblind attitudes. While racial-ethnic groups differed in reported levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…Rates of change in ethnic identity do not vary much across groups (Syed & Azmitia, 2009). Majority and minority individuals with more mature ethnic identity are more likely to nominate belonging and discrimination events than those with less mature ethnic identities (Syed & Azmitia, 2008; see also Charmaraman & Grossman, 2010). However, the implications of ethnic identity for other outcomes are often distinct among minority and majority group members, as stronger ethnic identification relates to more positive in-and out-group evaluations for minority individuals, but not for majority individuals (Kosic & Caudek, 2005;Verkuyten, 2005).…”
Section: Majority and Minority Differencesmentioning
confidence: 92%
See 1 more Smart Citation
“…Rates of change in ethnic identity do not vary much across groups (Syed & Azmitia, 2009). Majority and minority individuals with more mature ethnic identity are more likely to nominate belonging and discrimination events than those with less mature ethnic identities (Syed & Azmitia, 2008; see also Charmaraman & Grossman, 2010). However, the implications of ethnic identity for other outcomes are often distinct among minority and majority group members, as stronger ethnic identification relates to more positive in-and out-group evaluations for minority individuals, but not for majority individuals (Kosic & Caudek, 2005;Verkuyten, 2005).…”
Section: Majority and Minority Differencesmentioning
confidence: 92%
“…Ethnic identity exploration and pride are higher among minority group members than majority group members (Charmaraman & Grossman, 2010;Phinney, 1992;Syed & Azmitia, 2009). Minority individuals report more frequent and pervasive experiences with discrimination than do majority individuals (e.g., Greene, Way, & Pahl, 2006;Rosenbloom & Way, 2004) and the greater priority they give to ethnic identity may partially stem from their greater exposure to discrimination experiences.…”
Section: Majority and Minority Differencesmentioning
confidence: 96%
“…People of color who endorse colorblind racial attitudes may also become marginalized in diverse social settings (Charmaraman and Grossman 2010;Neville et al 2005;Tawa et al 2012b). For example, Tawa et al (2012b) found that among Asian Americans (N = 257), endorsing colorblind racial attitudes was related to lower overall collective self-esteem, less positive feelings toward Asian Americans, and were less likely to identify with the Asian American group.…”
Section: Effects Of Colorblind Racial Attitudes On Intergroup Behaviormentioning
confidence: 95%
“…These results support the idea that Asian Westerners have a heightened desire to fit in to Western society, and reactively respond to reminders that they do not fit in by affiliating with the prototypical members of Western society -that is, by identifying as relatively "White". Such findings build from previous research showing that Asian Westerners are less likely to identify with their own racial group than are other minorities (Charmaraman and Grossman, 2010;Jackson, 2002).…”
Section: Summary Of Findingsmentioning
confidence: 53%
“…Asian Westerners show the weakest identification with their racial group (Charmaraman and Grossman, 2010;Jackson, 2002; in this thesis, identified internally as White) and reject activism on behalf of their racial group (Lopez & Pantoja, 2004;Tropp et al, 2012). Thus, a logical step forward would be to propose that Asian Westerners may even feel some degree of prejudice towards their racial group due to their affiliation with the White majority.…”
Section: Theoretical Implications and Future Directionsmentioning
confidence: 99%